Isolation, optimization and recovery of astaxanthin from shrimp shell wastes of locally isolated Aeromonas hydrophila (Steiner) - Cheong, Jee Yin (2016)
Astaxanthin is a red pigment naturally produced by microalgae. Being part of the shrimp diet, this pigment was accumulated in their body, shells and eggs. The total amount of shell wastes discarded during processing could reach up to 40-50% of its body weight. Previously, astaxanthin was recovered from shrimp shells using lactic acid bacteria fermentation. This method promises a good return but has higher maintenance. Meanwhile aerobic bacteria fermentation has less maintenance and was less explored in this context. Astaxanthin in its free form is readily oxidised while astaxanthin in crustaceans appears to be in complexes (carotenoprotein, carotenolipoprotein and chitinocarotenoids) which is less prone to oxidation. The current aim was to recover astaxanthin from shrimp shell wastes through aerobic bacteria fermentation. In order to obtain astaxanthin from shrimp wastes, chitinase and protease were crucial to dechitinize and deproteinize the pigment from its stable complex structures. In this study, the first objective was to isolate potential shrimp shell degrading bacteria from shrimp shells. Bacteria were isolated from shrimp shells and screened using shrimp crab shell powder. A total of 19 isolates producing chitinase and protease were obtained. Potential isolates were then compared among each other using shrimp shell waste powder (SSWP) to seek for an optimum enzyme (chitianse and protease) producing isolate. The selected isolate was identified as Aeromonas hydrophila. Naturally, shrimp shells are calcified and may hinder further recovery of astaxanthin. Hence, the addition of cell disruptions was aimed to loosen the complex structure of shrimp shells. A dual effect “shell disruption” method was adopted where non-chemical shell disruption was applied on the wastes as pre-treatment followed by microbial enzyme disruption as the second. The amount of astaxanthin recorded after the application of shell disruptions was comparable between treatments of control (nonpretreated SSWP fermented with microbial enzyme) and autolysis (pre-treated SSWP with autolysis and microbial enzyme). The control treatment has resulted in 2.3 ± 0.1179μg/ml of astaxanthin recovery, while combined autolysis treatment and microbial enzyme yielded 2.11 ± 0.0961μg/ml. Since both treatments gave similar yield and were not significantly different, single shell disruption (control treatment) was sufficient to produce a good recovery. In order to enhance enzyme production and astaxanthin recovery, the culture media and conditions were also optimized. Optimization of the culture media and conditions was carried out using Response Surface Methodology analysis (RSM). The media was screened with various media supplements (nitrogen, inorganic salts and carbon sources) and concentrations (1, 3, 5, 7, 9% w/v) before optimizing with RSM. An optimum media containing 3% MSG, 1% glucose, pH 7.0 and 30 °C with a constant supply of 0.1% K2HPO4, 0.05% MgSO4.7H2O, and 9% SSWP was used to culture A. hydrophila. In comparison, by using the optimum culture astaxanthin recovery, chitinase and protease activity has increase up to 38.4%, 30% and 36% respectively as compared to un-optimized media. To achieve the main goal of this investigation, carotenoids were purified with thin layer chromatography (TLC) and the presence of astaxanthin was confirmed using high pressure liquid chromatography (HPLC). Carotenoids were obtained after bacteria fermentation on SSWP under optimized conditions and were soxhlet extracted with acetone and concentrated before subjecting to TLC. The best mobile phase in separating the pigments was hexane: acetone (3:1 v/v). The potential band for astaxanthin was obtained from TLC at Rf value of 0.33. This band was re-extracted in acetone and subjected to confirmation using HPLC with a reference standard. The presence of astaxanthin was confirmed at retention time of 15.5, 16.4, 17.4, and 18.3 minutes. In conclusion, astaxanthin can be recovered from shrimp shell waste with aerobic fermentation of A. hydrophila.